Analisis Efisiensi Pemasaran Produk Wine pada PT. Hatten Bali - GUTERRES, BELLA MARISOL MAZARELLO BARU; USTRIYANA, I NYOMAN GEDE; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018, 2018)
Marketing Efficiency Analysis of Wine Product by PT. Hatten Bali This research is aimed to acknowledge the system of the marketing channels and its functions, calculate the margins of the marketing and producer share to also analyzing the efficiency of overall products marketing system of hatten wine products by PT. Hatten Bali. The methods of data collection used are observation, interviews, and literatur reference. Methods for data collection in this study, were observation, interviews, and literatur reference. The samples using of 30 retailers around Denpasar City and Badung Regency chosen with snowball sampling. Data analyzing by descriptive qualitative and descriptive quantitative. The results showed that marketing channels of PT. Hatten Bali involving the retailers from hotels, villas, restaurants, and grocery stores. There are two types of marketing channels, type one is producer-consumer while type two is producer-retailers-consumer. The highest marketing margin from type two is recorded 181.000 idr per bottle while the lowest marketing margin coming from type one is 0.000 idr per bottle. The highest producer’s share is on type one by 100% and the lowest is on type two by 43.92%. The highest price efficiency is on type two by 222.73% and the lowest is on type one by 100%. The highest operational efficiency is on type two by 9.279,20% and the lowest recorded is on type one by 3.917,81%. Type one of marketing channels is the most efficient channel based on the analysis of margin marketing, produsen shares and price efficiency. While type two is the most efficient channel of marketing based on its operational efficiency analysis.